Advanced Techniques and Efficiency Assessment of Mechanical Processing - Saramak, Daniel; Pawełczyk, Marek; Niedoba, Tomasz (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Mechanical processing is just one step in the value chain of metal production, but to some exten,t it determines an effectiveness of separation through suitable preparation of the raw material for beneficiation processes through production of required particle sze composition and useful mineral liberation. The issue is mostly related to techniques of comminution and size classification, but it also concerns methods of gravity separation, as well as modeling and optimization. Technological and economic assessment supplements the issue.